(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
The effects of teaching methodologies based on Behavior Analysis are investigated over the learning of intraverbals, which are usually impaired in autistic children. The purpose of this research was to assess the effects of teaching tact and listener repertoires, by programming two different intervention packages for two pairs of autistic children, over the emergence of intraverbals consisting in listing category members. For two children from a tact condition, it was implemented the teaching of simple tacts, simple tacts with instructive feedback and category tacts. For two children from a listener condition, it was implemented simple listener responses, responses with instructive feedback and category identification as listener. No intraverbal emergence effect was demonstrated and the direct teaching of this repertoire demanded the use of many prompts (tact and echoic), producing increases in performance with variability for one participant and dependence of tact as prompt. Possibilities of methodological changes in the future are discussed.